Toward citizenship science education: what students do to make the world a better place? - Vesterinen, Veli-Matti; Tolppanen, Sakari; Aksela, Maija (International Journal of Science Education, 2016)
With increased focus on sustainability and socioscientific issues, dealing with issues related to citizenship is now seen as an important element of science education. However, in order to make the world a better place, mere understanding about socioscientific issues is not enough. Action must also be taken. In this study, 35 international gifted students—potential scientists—aged 15–19 were interviewed to investigate what they were doing to make the world a better place. The interviews were analyzed using qualitative content analysis with focus on students’ actions toward a better world, their rationalizations for such actions, and the role of science in the rationalizations. The analysis shows that students consciously take a wide range of actions, and that they see citizenship as a process of constant self-development. The three categories created to highlight the variation in the ways students take action were personally responsible actions, participatory actions, and preparing for future. Although many students saw that science and scientists play a big role in solving especially the environmental problems, most of them also discussed the structural causes for problems, as well as the interplay of social, economic, and political forces. The results indicate that citizenship science education should take the variety of students’ actions into consideration, give students the possibility to take individual and participatory action, as well as give students opportunities to get to know and discuss the ways a career in science or engineering can contribute to saving the world.